GeSe photovoltaics: doping, interfacial layer and devices. (18th July 2022) - Smiles, Matthew J.; Shalvey, Thomas P.; Thomas, Luke; Hobson, Theodore D. C.; Jones, Leanne A. H.; Phillips, Laurie J.; Don, Christopher; Beesley, Thomas; Thakur, Pardeep K.; Lee, Tien-Lin; Durose, Ken; Major, Jonathan D.; et al.
Abstract : Ag-doped GeSe has been successfully grown and compared to undoped GeSe with XRD, photoemissions, ICP-OES and CV. The undoped and Ag-doped GeSe were included in PV devices with the champion device structure and J – V curve shown. Abstract : Germanium selenide (GeSe) bulk crystals, thin films and solar cells are investigated with a focus on acceptor-doping with silver (Ag) and the use of an Sb2 Se3 interfacial layer. The Ag-doping of GeSe occurred by a stoichiometric melt growth technique that created Ag-doped GeSe bulk crystals. A combination of capacitance voltage measurements, synchrotron radiation photoemission spectroscopy and surface space-charge calculations indicates that Ag-doping increases the hole density from 5.2 × 10 15 cm −3 to 1.9 × 10 16 cm −3 . The melt-grown material is used as the source for thermally evaporated GeSe films within solar cells. The cell structure with the highest efficiency of 0.260% is FTO/CdS/Sb2 Se3 /undoped-GeSe/Au, compared with solar cells without the Sb2 Se3 interfacial layer or with the Ag-doped GeSe.